Factors Causing Boredom in Learning Fiqh in Grade VII Students at MTs Nurul Ihsan Tanjung Jabung Timur Jambi - Sri Wahyuni; Rapiko Rapiko (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Learning is a process of behavioral change that occurs through the interaction of individuals with the surrounding environment, learning is understood as an activity carried out by someone to acquire new knowledge, attitudes, and skills through experience and training. Meanwhile, learning is a process of interaction between educators and students that involves various components such as teaching materials, methods, learning strategies, media, and learning resources in an environment that can support the achievement of the educator's goals. The factors causing learning boredom consist of two factors, namely internal factors such as monotonous teacher methods and external factors originating from students' lack of interest in learning or the influence of gadgets. Therefore, teachers must have creative and innovative ideas so that students remain enthusiastic and focused in learning, This study uses qualitative research which uses observation, interviews and researchers, in the discussion of this research article, it focuses on two important points, namely, the factors causing learning boredom, and teacher efforts to overcome boredom.